Kesetaraan Gender dan Sikap terhadap AI dalam Rangka Bela Negara Pada Generasi Z - Agnes Yolanda Hartono, Agnes; Olivia Kusuma, Carla; Oktavia, Stephanie; Arianto, Deborah; Chezya, Glaeny; Markus Idulfilastri, Rita; Hendra, Pamela Hendr (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2025)
This study examines the influence of gender equality on Generation Z's attitudes toward artificial intelligence (AI) in the context of digital national defense. A total of 171 university students aged 18–25 years old were involved as respondents, consisting of 95 women and 76 men. Analysis using the Mann-Whitney test showed a significant difference in attitudes toward AI between men and women, where women scored higher (mean rank = 93.10) than men (mean rank = 77.13). However, no significant difference was found in the level of gender equality between the two. The results of the correlation test showed a strong positive relationship between gender equality and attitudes toward AI, with a correlation value of 0.689. In addition, the results of the regression analysis showed that gender equality contributed 48% to the formation of Generation Z's attitudes toward AI. This means that the higher the level of gender equality, the more positive their attitudes toward the use of artificial intelligence-based technology. Other factors outside the gender equality variable were not examined in this study. These findings confirm that gender equality plays a significant role in shaping Generation Z's readiness and participation in digital national defense. The results of this study are expected to form the basis for the development of inclusive digital literacy and gender-equitable technology policies in Indonesia.